Statin therapy in multimorbid older patients with polypharmacy- a cross-sectional analysis of the Swiss OPERAM trial population - Adam, Luise; Baretella, Oliver; Feller, Martin; Blum, Manuel Raphael; Papazoglou, Dimitrios David; Boland, Benoit; Aujesky, Drahomir; Baggio, Stéphanie; Rodondi, Nicolas (Frontiers in Cardiovascular Medicine, 2023)
Background Statin therapy in multimorbid older individuals with polypharmacy is controversial, particularly in primary prevention of cardiovascular disease. Thereby, physicians must weigh potential benefits against potential side effects, drug-drug interactions, and limited life expectancy. Aim To assess the prevalence and determinants of potentially inappropriate statin therapy in multimorbid older patients. Methods We conducted a cross-sectional analysis of patients aged ≥70 years with multimorbidity and polypharmacy in the Swiss study center of OPERAM, a cluster-randomized trial on pharmacotherapy optimization to reduce drug-related hospital admissions. We assessed potential underuse (no statin but formal indication) and potential overuse (statin but no formal indication, including predicted >60% one-year mortality based on the Walter Score) based on current guidelines for patients in secondary and primary cardiovascular prevention. We assessed the association of potential statin overuse and underuse with six patient characteristics (age, gender, number of diagnoses, number of medications, mental impairment, being housebound) in LASSO-selection analyses. Results Of 715 multimorbid older adults (79.7 ± 6.5 years, 39.9% women), 337 (47%) were on statin. Statin therapy was appropriate in 474 (66.3%), underused in 130 (18.2%), and overused in 111 (15.5%) patients. In participants in secondary cardiovascular prevention (n = 437), being female (odds ratio [OR] 2.65, 95% confidence interval [CI] 1.67–4.22) was significantly associated with potential underuse while being housebound (OR 3.53, 95%CI 1.32–9.46) and taking ≥10 medications (OR 1.95,95%CI 1.05–3.67) were associated with potential overuse. In participants in primary cardiovascular prevention (n = 278), 28.1% were potentially under- (9%) or overusing (19%) a statin, with no identified risk factor. Conclusion A third of hospitalized multimorbid older patients with polypharmacy potentially (either) overused or underused statin therapy. Among patients in secondary cardiovascular prevention, women were at risk for potential statin underuse. Housebound patients and those taking ≥10 medications were at risk for potential overuse of a statin. Physicians should carefully evaluate the indication for statin prescription in multimorbid older patients with polypharmacy.